Implemantasi Peraturan Daerah Kabupaten Bulungan Nomor 06 Tahun 2009 Tentang Penataan Pedagang Kaki Lima - Kartini Maharani Abdul; Yunita Kurniasari Sirajudin (FISIP UWP, 2022)
This study aims to determine the implementation of the Bulungan Regency Regional Regulation No. 6 of 2009 concerning the Arrangement of Street Vendors a case study of the Tanjung Selor city afternoon market). The data used in this study were obtained by observation based on field conditions as well as interview and documentation techniques. This research was conducted in the afternoon market area, this research is to explain the research data in the form of complete, systematic, and easy sentences to understand and interpret so that a conclusion can be drawn. Data analysis in this study was carried out with a qualitative approach. The data obtained will be analyzed qualitatively, namely by analyzing the data and then describing the phenomena that occur. From the results of this study, it is known that the implementation of the Bulungan Regency Regional Regulation Number 6 of 2009 concerning the Arrangement of Street Vendors regarding the arrangement of street vendors has not been implemented effectively.